Investigation of the capabilities of a supersonic transport system in a rarefied environment - Timirgaleeva Rena; Lukyanova Yelena; Bukreev Igor; Selivanov Victor; Kazak Anatoliy (E3S Web of Conferences, 2023)
The paper is devoted to the study of problems in organizing high-speed ground transport traffic. The solution to this problem may be the organization of a combined transport system, which involves the movement of a transport unit in a rarefied environment of limited space, using the principles of magnetic levitation. The use of such a system will significantly increase the speed of a transport unit up to the supersonic range due to the following factors: reduced aerodynamic air resistance when moving; the absence of direct contact of the transport unit with the lower structure of the track and, as a result, the complete absence of friction; separate dedicated lines allow the use of structures that allow for a significant increase in freight traffic. The paper explores the possibilities of developing the basic principles of movement of a transport system based on magnetic levitation in a rarefied environment, modeling key processes, determining the main parameters of a new transport system and establishing their optimal ratio, reduced to conditions of safe and energy-efficient operation. As well as an assessment of possible risks associated with the use of this type of transport, both for freight and passenger transportation.